Similar changes of gene expression in human skeletal muscle after resistance exercise and multiple fine needle biopsies - Friedmann-Bette, Birgit; Schwartz, Fides Regina; Eckhardt, Holger (Journal of applied physiology, 2012)
Repeated biopsy sampling from one muscle is necessary to investigate muscular adaptation to different forms of exercise as adaptation is thought to be the result of cumulative effects of transient changes in gene expression in response to single exercise bouts. In a crossover study, we obtained four fine needle biopsies from one vastus lateralis muscle of 11 male subjects (25.9 ± 3.8 yr, 179.2 ± 4.8 cm, 76.5 ± 7.0 kg), taken before (baseline), 1, 4, and 24 h after one bout of squatting exercise performed as conventional squatting or as whole body vibration exercise. To investigate if the repeated biopsy sampling has a confounding effect on the observed changes in gene expression, four fine needle biopsies from one vastus lateralis muscle were also taken from 8 male nonexercising control subjects (24.5 ± 3.7 yr, 180.6 ± 1.2 cm, 81.2 ± 1.6 kg) at the equivalent time points. Using RT-PCR, we observed similar patterns of change in the squatting as well as in the control group for the mRNAs of interleukin 6 (IL-6), IL-6 receptor, insulin-like growth factor 1, p21, phosphofructokinase, and glucose transporter in relation to the baseline biopsy. In conclusion, multiple fine needle biopsies obtained from the same muscle region can per se influence the expression of marker genes induced by an acute bout of resistance exercise.